Faculty perceptions and conveyance of academic ethics to students in distance learning - Maigi Lepik; Kateriina Rannula; Liina Männiksaar (Proceedings of the Estonian Academy of Sciences)
Emphasising academic ethics throughout the educational process is crucial for all learners. The applied research project at Tallinn Health University of Applied Sciences, titled Ê»Academic ethics as lecturerâs toolkit in the teaching process â adapting to the changing environmentÊ¼, explores how faculty perceive ethical values and how they communicate these values during distance learning. The study aims to describe how faculty perceive and convey academic ethics in the context of distance learning. An inductive thematic analysis was employed to analyse the data from twenty semi-structured interviews conducted with faculty members of Tallinn Health University of Applied Sciences. The analysis revealed four main categories that describe faculty perceptions regarding the nature and conveyance of academic ethics to students during distance learning. The interview data indicated that faculty primarily rely on peer support and prior experiences when navigating ethical issues. The interviews consistently reflected four key themes: academic integrity, ethical communication, peer collaboration in maintaining academic discourse, and the promotion of and adherence to established guidelines. Faculty also highlighted ethical dilemmas in distance learning, such as academic dishonesty during examinations and the challenges of monitoring student activities online. The study identified several key factors, including faculty awareness of academic ethics, the importance of colleague and institutional support, and the unique ethical challenges posed by distance learning. The findings suggest that faculty not only comprehend academic ethics but also actively promote these values, thereby enhancing studentsÊ¼ understanding of their significance.